MY SAY: Of junk food, obesity and climate change - Abd Razak, Dzulkifli (2009)
There are now reports showing that during these troubled economic times, instant and junk food outlets are making a fast buck with their rather inexpensive (never mind unhealthy) meals. One business chain claims to have achieved higher profit, thanks to the numbers of clients patronising its joints worldwide. New and cheap menus are also appearing on the table, adding to what is already available. This seems to make economic sense except that it now has a greater ramification than previously understood. How so?